2003
DOI: 10.2307/3803076
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Status of Harbor Seals in Washington State: 1978-1999

Abstract: In the first half of the twentieth century, harbor seal ( Phoca vitulina richardsi ) numbers were severely reduced in Washington state by a state-financed population control program. Seal numbers began to recover after the cessation of bounties in 1960 and passage of the Marine Mammal Protection Act (MMPA) in 1972 . From 1978 to 1999 , aerial surveys were flown at midday low tides during pupping season to determine the distribution and abundance of harbor seals in Washington. We used exponential and generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
165
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(168 citation statements)
references
References 0 publications
3
165
0
Order By: Relevance
“…The observed growth rates in several, apparently closed, harbour seal populations have approached 12-13% p.a. (Heide-Jørgensen and Härkönen 1988;Reijnders 1992b;Boveng et al 2003;Härkönen et al 2002;Jeffries et al 2003). This probably represents the intrinsic rate of increase of an undisturbed and unconstrained harbour seal population in the absence of density dependent effects.…”
Section: Englandmentioning
confidence: 99%
“…The observed growth rates in several, apparently closed, harbour seal populations have approached 12-13% p.a. (Heide-Jørgensen and Härkönen 1988;Reijnders 1992b;Boveng et al 2003;Härkönen et al 2002;Jeffries et al 2003). This probably represents the intrinsic rate of increase of an undisturbed and unconstrained harbour seal population in the absence of density dependent effects.…”
Section: Englandmentioning
confidence: 99%
“…Demersal fi sh species in Puget Sound are consumed by elasmobranchs, such as Spiny Dogfi sh (Squalus acanthias) and Bluntnose Sixgill Shark (Hexanchus griseus), and marine mammals, such as the harbor seal (Phoca vitulina; Bromaghin et al, 2013;Howard et al, 2013) and California sea lion (Zalophus californianus), but we are unaware of any abrupt changes in predator densities in Port Madison to explain these patterns. Jeffries et al (2003) reported a monotonic increase in harbor seal abundance in Puget Sound from the late 1970s to the 1980s that was followed by little change in abundance during the mid-to late 1990s. Fourth, groundfi sh densities can be sensitive to water quality, especially to oxygen concentrations at the seafl oor that result in distributional shifts to normoxic conditions (Breitburg et al, 2009;Essington and Paulsen, 2010), and chronic hypoxia exposure could diminish productivity of groundfi sh prey (Diaz and Rosenberg, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It is critical that surveys are repeated as frequently as is financially viable to maximize our power to detect trends. Replicate counts within a survey region have been used to obtain more precise population estimates and periodic replicate surveys have been used to examine trends (Pitcher 1990, Frost et al 1999, Adkison et al 2003, Jeffries et al 2003. Studies on trend analyses of harbour seal count data suggest that even surveying annually (with 2-3 replicate surveys) it will take at least 5 years to robustly estimate annual trends greater than 5%, but as changes of more than 5% per annum are unusual in stable seal populations then realistically it will take even longer than 5 years (Adkison et al 2003, ICES 2003.…”
Section: National Monitoring Programmementioning
confidence: 99%
“…However, these counts have varied in location, consistency, timing and methodology and could not provide complete national or island-wide perspectives on population size and distribution. , 1997, Huber 1995, Jeffries et al 2003, Adkinson et al 2003, Hayward et al 2005. While breeding season counts provide reliable estimates of abundance as well as valuable pup production data, Härkönen et al (1999) concluded that in nonstable age-structured populations the influence of the differential haulout behaviour on estimating abundance is likely to be greater during the breeding period than during the moult period.…”
mentioning
confidence: 99%